2013
DOI: 10.1016/j.spinee.2013.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically guided anterior atlantoaxial transarticular screws: a feasibility and trajectory study using CT-based simulation software

Abstract: BACKGROUND CONTEXT: Anterior transarticular screw (ATAS) fixation has been suggested as a viable alternative to posterior stabilization. However, we are not aware of previous reports attempting to establish the usefulness of specific fluoroscopic landmark-guided trajectories in the use of ATAS, and we could find no reference to it in a computerized search using MEDLINE. PURPOSE: To determine the anatomic feasibility of ATAS placement using defined fluoroscopic landmarks to guide screw trajectory. STUDY DESIGN:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It provides a safer and more appropriate environment with high fusion rates and only minor complications for challenging cases such as patients with osteolysis in infectious or tumorous conditions, aberrant vertebral artery, and/or narrow pars interarticularis. 83 However, there are concerns about safe screw dimension, insertion, and trajectory. One study analyzed the feasibility of anterior transarticular screw fixation in 100 patients and recommended reliable fluoroscopic landmarks with minor complications and threshold lengths of C1 purchase screws during this procedure.…”
Section: Treatmentsmentioning
confidence: 99%
“…It provides a safer and more appropriate environment with high fusion rates and only minor complications for challenging cases such as patients with osteolysis in infectious or tumorous conditions, aberrant vertebral artery, and/or narrow pars interarticularis. 83 However, there are concerns about safe screw dimension, insertion, and trajectory. One study analyzed the feasibility of anterior transarticular screw fixation in 100 patients and recommended reliable fluoroscopic landmarks with minor complications and threshold lengths of C1 purchase screws during this procedure.…”
Section: Treatmentsmentioning
confidence: 99%
“…Two years later, the same team performed a biomechanical study and confirmed the effectiveness of this technique in atlantoaxial stabilization [4]. Since then, some modification in surgical techniques using minimally invasive or percutaneous surgical procedures have been reported [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a securer and extra suitable milieu with high fusion rates and negligible hitches for difficult cases like in patients with osteolysis in infectious or tumorous disorders, aberrant vertebral artery, and/or narrow pars interarticularis. 1 , 8 , 50 However, safe screw dimension, insertion, and trajectory are the major short comings with the approach. 1 …”
Section: Discussionmentioning
confidence: 99%